Under the Counter and Over the Border
VIII, 192 p.
Keywords: Although the illicit arms trade has evolved over recent years, despite the end of the Cold War it appears to be as vibrant as ever. From Bosnia and Kosovo to Angola and Sierra Leone, illicit arms flows have played a key role in areas of contemporary instability and violence. Against this background, this volume brings together studies of several key issues relating to this trade: the changing nature of the illicit arms trade; the origins of the Iran-Contra affair; the flow of illicit arms from post-communist Russia; the role of France in arming the genocide in Rwanda; the question of the role of private security companies in areas of instability; and the prospects of controlling the illicit trade in small arms. This timely volume will be essential reading for courses in Criminology, War and Peace Studies, International Politics, and African and other Area Studies which deal with arms trafficking and conflict issues.